2010
DOI: 10.1186/1471-2229-10-172
|View full text |Cite
|
Sign up to set email alerts
|

Potassium deficiency induces the biosynthesis of oxylipins and glucosinolates in Arabidopsis thaliana

Abstract: BackgroundMineral fertilization and pest control are essential and costly requirements for modern crop production. The two measures go hand in hand because plant mineral status affects plant susceptibility to pests and vice versa. Nutrient deficiency triggers specific responses in plants that optimize nutrient acquisition and reprogram metabolism. K-deficient plants illustrate these strategies by inducing high-affinity K-uptake and adjusting primary metabolism. Whether and how K deficient plants also alter the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 65 publications
3
61
1
3
Order By: Relevance
“…The addition of silicon was shown to trigger priming of the JA-mediated herbivory defense in rice (Ye et al, 2013). Potassium deficiency in Arabidopsis increased the expression of several JA-responsive genes, enhanced the synthesis of several oxylipins in leaves, including JA, and was associated with reduced damage by thrips (Armengaud et al, 2004Troufflard et al, 2010). Sulfur deficiency resulted in an enhanced expression of several genes involved in JA synthesis, and mutation affecting sulfur metabolism influenced basal JA levels (Hirai et al, 2003;Maruyama-Nakashita et al, 2003;Nikiforova et al, 2003;Rodríguez et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The addition of silicon was shown to trigger priming of the JA-mediated herbivory defense in rice (Ye et al, 2013). Potassium deficiency in Arabidopsis increased the expression of several JA-responsive genes, enhanced the synthesis of several oxylipins in leaves, including JA, and was associated with reduced damage by thrips (Armengaud et al, 2004Troufflard et al, 2010). Sulfur deficiency resulted in an enhanced expression of several genes involved in JA synthesis, and mutation affecting sulfur metabolism influenced basal JA levels (Hirai et al, 2003;Maruyama-Nakashita et al, 2003;Nikiforova et al, 2003;Rodríguez et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…15 The K C nutritional status is linked to the ethylene, cytokinin, jasmonic acid and auxin signaling pathways, thus leading to developmental and physiological alterations. [16][17][18] Moreover, it presumably influences plant disease resistance. 19 When grown under limiting K C supply, total root size was reduced in 26 investigated natural Arabidopsis accessions, but the degree of reduction and the root architectural response to K C limitation strongly differed between accessions.…”
Section: Introductionmentioning
confidence: 99%
“…The compounds reduce severity of pathogen through disruption of spores and the hyphal contents mainly for the fungal pathogens (Bailey 1789-1791) [2] . Other secondary metabolites that confer resistance against the pathogenic microbes are the volatile organic compound for instance methyl salicylate and methyl jasmonate as they help in limiting conidial germination of the pathogenic fungi (Quintana-Rodriguez et al 250-260; Neri et al [30][31][32][33][34][35] [25,20] . More interactions have shown that some pathogenic microbes have evolved survival mechanisms against the plant defensive compound.…”
Section: Interaction With Pathogenic Microbesmentioning
confidence: 99%